Strategi Komunikasi Interpersonal Taman Edukasi Dalam Menarik Wisatawan Pada Objek Wisata Keju Lasi Kecamatan Candung Kabupaten Agam - Zakiatus Shaufi; Darul Ilmi; Junaidi Junaidi; Yusuf Afandi (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to look at the educational park's interpersonal communication strategy in attracting tourists to this cheese lation tourist attraction, and based on field observations of data there are strategies set by guides in the lasi cheese educational park so that tourists are guided and get well-directed related to the object. cheese tour. This type of research is field research with a qualitative approach, namely describing what is about a situation. In this study the authors describe the Educational Park Interpersonal Communication Strategy in Attracting Tourists at the Cheese Lasi Tourism Object, Cdung District, Agam Regency. In collecting data, the authors used observation and interview techniques with informants related to the Educational Park Interpersonal Communication Strategy in Attracting Tourists at the Lasi Cheese Tourism Object. The results of the research or the conclusions of the research are that the Interpersonal Communication Strategy of the Educational Park in Attracting Tourists at the Cheese Lasi Tourism Object, Cdung District, Agam Regency consists of, first, the communication strategy of choosing and assigning communicators, identifying targets, selecting communication media. second, obstacles in interpersonal communication in the form of technical disturbances, physical disturbances, semantic disturbances, status barriers, frame of mind obstacles. Third, efforts to attract lasi cheese attractions